The role of proactive personality on transformational leadership and innovative work behavior - Farhanah Murniasih (Psychocentrum Review, 2023)
The industrial revolution 4.0 also requires the business world to move more dynamically and forces businessmen in the industry to move faster. The Covid-19 pandemic has also changed trends in the world of work, it is currently moving towards digitization and remote work. Therefore, workers are encouraged to continuously improve their skills and abilities in facing future challenges. One of the factors that can help companies to survive in this crisis is by innovating. The study aims to understand the effect of proactive personality on transformational leadership and innovative work behavior relationship. The instruments used were Multifactor Leadership Questionnaire Form 5x scale, Proactive Personality Scale and Innovative Work Behavior Scale adapted into Indonesian. The study sample consisted of 177 responses used for data analysis in SPSS ver 23 using PROCESS by Hayes. Results showed that proactive personality fully mediates transformational leadership and innovative work behavior relationship. The implications, limitations and suggestions for further research are discussed as follows.